Analysis of The Puncak Tumada Drinking Water Network System Using Epanet Software - Muhammad Abdu; Aswad Asrasal; Muhammad Sayfullah (SCEJ (Shell Civil Engineering Journal), 2022)
Tumada village is a village located in kapontori district of buton regency, with a population of 630 people where clean water needs are obtained from access to water sourced from springs by the method of flowing using pipes by gravity so that water needs can be met. The height of the tank source is at the high point of Elv = ± 24.27 MDPL while the highest place for water use is Elv = ± 50 MDPL. Those who do not get this water source are those who are located in sma and in the peak area of tumada where the number of KK = 7 To improve water management, the water is first accommodated in the tank and flowed by gravity, where the elevation elevation of the Elv tank placement = ± 63. With the analysis obtained pipe sizes of 12.5 mm, 25 mm, 50 mm with a tank capacity of 6000 liters and pump power can be used with a head of 50 m and flow of 0.5 LPS in addition to that a minimum press of 9.5 m and speed respectively for the main pipe of 0.28 m / s and pipe Divider of 0.16 m / s and discharge in the pipe flow of 0.56 LPS for the main and for divisors of 0.03 LPS and 0.02 LPS.